(untitled) (International Journal of Research in Pharmaceutical Sciences and Technology, 2026)
Snakebite envenomation remains a major public health burden, particularly in developing countries where conventional antivenom therapy is costly, poorly accessible, and often ineffective against local tissue damage. This study explored the phytochemical basis of the antivenom potential of Tylophora indica (Burm.f.) Merr., a medicinal plant traditionally used in the management of various ailments. Whole-plant extracts were prepared using petroleum ether and ethanol as solvents, which on further phytochemical evaluation confirmed the presence of secondary metabolites, namely alkaloids, flavonoids, terpenoids, glycosides, phenols and saponins etc. with ethanolic extract exhibiting rich phytochemical profiles. Ethanolic extract subjected to gas chromatography–mass spectrometry (GC-MS), showed the presence of major phytoconstituents including, hexadecanoic acid, phytol, lupeol, and beta-elemene, among others. The in-silico evaluation for the potential antivenom action mechanism were performed applying molecular docking methodology against two key venom-associated enzyme targets, phospholipase A2 (PLA2) and hyaluronidase (2PE4). Lupeol showed the strongest binding affinity against PLA2 (−9.6 kcal/mol, estimated Ki ≈ 91.87 nM), while beta-elemene and other compounds showed moderate affinity against 2PE4, interacting mainly through hydrophobic contacts. These findings suggest that phytoconstituents of Tylophora indica, particularly lupeol, may inhibit key venom enzymes and contribute to anti-venom activity, supporting the plant’s potential as a lead source for developing plant-based antivenom therapeutics.